Internal transcribed spacer guided multiplex PCR for species identification of Convolvulus prostratus and Evolvulus alsinoides - Sonal Sharma; Neeta Shrivastava (Elsevier, 2016)
Shankhpushpi is a reputed drug from an Indian system of medicine for treating mental disorders and enhancing memory. Two herbs, namely Convolvulus prostratus Forssk. and Evolvulus alsinoides (L.) L., are commonly known as Shankhpushpi. Ambiguous vernacular identity can affect the scientific validity of the Shankpushpi-based herbal drug therapy. In the present investigation, a novel and sensitive multiplex PCR method based on polymorphism in the internal transcribed spacer (ITS) region was developed to establish the molecular identity of C. prostratus and E. alsinoides. DNA was isolated and the ITS region was amplified, sequenced and assembled. Sequences were aligned to identify variable nucleotides in order to develop plant-specific primers. Primers were validated in singleplex reactions and eventually a multiplex assay was developed. This assay was tested for sensitivity and validated by amplifying DNA isolated from the simulated blended powdered plant material. Primers developed for C. prostratus resulted into a 200 bp amplicon and 596 bp for E. alsinoides. The assay was found to be sensitive enough for amplification of low quantities of DNA. The method can detect 10% of the mixing of plants with each other in blended material. This PCR assay can be used for rapid botanical identification of Shankhpushpi plant materials and will improve evidence-based herbal drug therapy.